RESILIÊNCIA DO AMBIENTE CONSTRUÍDO EM HABITAÇÕES DE INTERESSE SOCIAL NO BAIRRO SHOPPING PARK (UBERLÂNDIA/MG) - Bortoli, Karen; Villa, Simone (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This paper aims to present the impacts, vulnerabilities and adaptive capacities of the Social Housing Complex of the Shopping Park neighborhood (Uberlândia, MG) which conditionates its current resilience, observed as preliminary results from a master's reserach in progress and obtained throught advanced Post-Occupancy Evaluation (POE) techniques. Additionally, the concepts of climatic and environmental adequacy are presented as recommendations for resilience in the built environment, leading the observation about what should be maintained, improved or refined in order to achieve a desirable resilience status on the case study.